2021
DOI: 10.1177/00952443211029039
|View full text |Cite
|
Sign up to set email alerts
|

PP/POE thermoplastic elastomer prepared by dynamic vulcanization and its flame retardant modification

Abstract: Flame retardant thermoplastic elastomer (TPE) with excellent mechanical properties and thermal oxidative aging resistance was prepared by dynamic vulcanization technology with ethylene-octene copolymer (POE) and polypropylene (PP) as raw materials. The paper first discussed the effect of the amount of vulcanizing agent on the properties of PP/POE TPE. Based on the study of tensile strength, elongation at break, cross-section morphology, processability and aging properties of TPE, it was found that the TPE prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…14,15 These strong, physical cross-links provide EOCs with elasticity and strength, and EOCs are desirable as low-cost impact modifiers and tougheners in thermoplastic elastomers, foams, and shape memory polymers for applications like footwear, cushioning, and catheters. [16][17][18][19][20][21][22][23] EOCs are common components in blends with other polymers such as polypropylene (PP), [24][25][26][27][28] ethylene propylene diene monomer (EPDM) rubber, [29][30][31][32] ethylene-vinyl acetate copolymer (EVA), [33][34][35] and polydimethylsiloxane (PDMS). 36,37 Like PE, EOCs and their blends may be vulcanized or covalently crosslinked using radical initiators such as peroxides to enhance properties like elasticity and temperature resistance.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 These strong, physical cross-links provide EOCs with elasticity and strength, and EOCs are desirable as low-cost impact modifiers and tougheners in thermoplastic elastomers, foams, and shape memory polymers for applications like footwear, cushioning, and catheters. [16][17][18][19][20][21][22][23] EOCs are common components in blends with other polymers such as polypropylene (PP), [24][25][26][27][28] ethylene propylene diene monomer (EPDM) rubber, [29][30][31][32] ethylene-vinyl acetate copolymer (EVA), [33][34][35] and polydimethylsiloxane (PDMS). 36,37 Like PE, EOCs and their blends may be vulcanized or covalently crosslinked using radical initiators such as peroxides to enhance properties like elasticity and temperature resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Flame-retardant materials containing halogen elements often achieve the purpose of flame-retardance through the gas phase. 115 Yan et al 53 reported the fabrication of a cathode based on the ring-opening reaction and the following nucleophilic aromatic substitution reaction of tetrafluoro hydroquinone (TFHQ) (Fig. 3b).…”
Section: Strategies To Realize Flame-retardant Cathodes In Lsbsmentioning
confidence: 99%
“…11 Among various types of TPEs, polyolefin elastomer (POE) is produced using metallocene catalysts, resulting in an eethylene-octene copolymer structure. POE offers a unique combination of high modulus and flexibility 12,13 and serves as the matrix material in UHMWPE composites, providing flexibility and lightweight.…”
Section: Introductionmentioning
confidence: 99%